Effect of Impact Cavity Shape Induced by Supersonic Oxygen Jet on the Dynamic Characteristics of Molten Bath in Converter. Issue 9 (2nd September 2021) - Sun, Jiankun; Zhang, Jiangshan; Lin, Wenhui; Cao, Lingling; Feng, Xiaoming; Liu, Qing
Abstract : The cover image illustrates the numerical simulation of a four‐hole supersonic jet impinging on the molten steel bath during the top‐blown converter steelmaking process. The modified cavity shape index is put forward to quantitatively describe the scattered cavities profile. Furthermore, the relationship between the cavity shape and dynamic characteristics of the molten bath is also analyzed. Further details can be found in the article, number 2100179, by Qing Liu, and co‐workers.